The Salafis and the Preservation of Isn?d Tradition (KEMANUSIAAN The Asian Journal of Humanities, 2020)
Transmitting Hadith with full isn?d (chain of transmitters) connecting back to Prophet Muhammad (peace and blessings of Allah be upon him) has been considered as an exclusive privilege for Muslims and one of the significant traditions of past Ahl al-Hadith (scholars of Hadith). In modern times, when isn?d are no longer examined to determine the authenticity of Hadiths, the tradition is still preserved by the scholars with Sufi inclination whose credentials and works have been widely renowned. On the other hand, an indifference shown by some of modern Salafis has been used by their opponents to question their qualification and expertise in Hadith criticism. This article aims to examine how Salafis assess the importance of isn?d tradition in modern times. This research is qualitative in nature. The data was mainly collected from modern and pre-modern biographical dictionaries. The research finds that pre-modern Salafis showed equal interest in preserving the living isn?d tradition to their Sufi peers albeit a minority of them did ignore its importance. A more careful examination suggests that this minority opinion was not a total rejection of isn?d tradition, instead, it should be seen as contention over excessive remarks regarding the importance of isn?d, as well as a prevention from endorsing Sufism.